1997
DOI: 10.1007/s004420050089
|View full text |Cite
|
Sign up to set email alerts
|

Negative effects of ant foraging on spiders in Douglas-fir canopies

Abstract: Spiders and ants are potential competitors and mutual predators. Indirect evidence from previous research has suggested that ant foraging may significantly lower the abundance of arboreal spiders in young Douglas-fir plantations in western Oregon. This study tested the effect of foraging by ants, dominated by Camponotus spp., on spider assemblages in Douglas-fir canopies in a 5-month ant-exclusion experiment. The biomass of potential prey organisms on foliage, dominated by Psocoptera, increased significantly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 49 publications
5
101
1
1
Order By: Relevance
“…Many orb-web spiders store the remains of prey in their webs [9], and these items, together with other prey entangled in the web, the protein-rich composition of silk [8] and the resident spider itself, provide nutritional resources for predators and scavengers, particularly small kleptoparasitic Argyrodes spiders [10,11]. Ants can be major predators of spiders [12][13][14], and workers of some species invade spider webs, establishing foraging trails on the non-sticky silk strands to access large caches of food [15,16]. Nevertheless, ants are rarely reported foraging on the webs of orb-web spiders, despite their diversity, abundance and vulnerability during moulting [17][18][19][20], and the superabundance and formidable predatory capabilities of ants [21].…”
Section: Introductionmentioning
confidence: 99%
“…Many orb-web spiders store the remains of prey in their webs [9], and these items, together with other prey entangled in the web, the protein-rich composition of silk [8] and the resident spider itself, provide nutritional resources for predators and scavengers, particularly small kleptoparasitic Argyrodes spiders [10,11]. Ants can be major predators of spiders [12][13][14], and workers of some species invade spider webs, establishing foraging trails on the non-sticky silk strands to access large caches of food [15,16]. Nevertheless, ants are rarely reported foraging on the webs of orb-web spiders, despite their diversity, abundance and vulnerability during moulting [17][18][19][20], and the superabundance and formidable predatory capabilities of ants [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, ants may also interact with spiders. In an experimental study in Oregon, Halaj et al (1997) showed that competition can occur between canopy-living ants and spiders in Douglas-fir (Pseudotsuga menziesii). Although the abundance of hunting spiders (mostly Salticidae) increased significantly in trees without ants, web-building spiders (e.g., Theridiidae, Araneidae, Linyphiidae) did not respond numerically to ant removal.…”
Section: Discussionmentioning
confidence: 99%
“…Ant presence can affect hunting behavior of other organisms (Halaj et al 1997) and cause higher occupation of prey refugia (Crutsinger and Sanders 2005). In these cases, however, herbivory is increased by aphid presence and therefore the association is likely to impact the host plant in a negative way.…”
Section: Greenhouse Experimentsmentioning
confidence: 99%